Hadith-Based Moral Integration in Islamic Education: A Faith-Based Framework for Achieving the SDGs - Irfan Yuhadi; Nurul Budi Murtini; Dananjaya, Ardian; Ariangga Ramadhansyah; Muhammad Raiham Al Farez; Seno Bayu Aji; Hastowohadi (Profetika: Jurnal Studi Islam, 2025)
Objective: Develop moral integration based on hadith in Islamic education through a religious approach to support the achievement of the Sustainable Development Goals (SDGs), especially in the aspects of social justice, environmental sustainability, and governance integrity. Theoretical framework:  The research relies on the prophetic moral concept sourced from hadith as the foundation of character formation, combined with a religious approach in Islamic education, as well as the SDGs value framework as an orientation for sustainable global development. Literature review: The literature review includes the study of moral values in hadith, the role of Islamic education in character building, the concept of social and environmental ethics from an Islamic perspective, and the relationship of religious values to the sustainable development agenda. Methods: The research method uses a qualitative approach with a library research design, which involves analyzing relevant literature sources in the form of hadiths, books, and previous research to formulate a conceptual integration model. Results: The results of the study show that prophetic moral values such as justice, trust, social responsibility, and environmental ethics have a fundamental role in the formation of students' character, as well as the moral integration based on hadith, not only forms ritual piety but also ethical, reflective, and transformative awareness in educational and social life. Implications:  Hadith-based moral integration can strengthen ethical orientation in achieving the SDGs and has strategic relevance in the development of a sustainable Islamic education curriculum. Novelty: Conceptual integration between hadith-based morality in Islamic education with a religious approach that bridges prophetic ethics and the goals of the SDGs in one integrated theoretical framework.